A Comparative Interaction between Copper Ions with Alzheimer's β Amyloid Peptide and Human Serum Albumin - G. Rezaei Behbehani; L. Barzegar; M. Mohebbian; A. A. Saboury (Bioinorganic Chemistry and Applications)
The interaction of Cu2+ with the first 16 residues of the Alzheimer's amyliod β peptide, Aβ(1–16), and human serum albumin (HSA) were studied in vitro by isothermal titration calorimetry at pH 7.2 and 310 K in aqueous solution. The solvation parameters recovered from the extended solvation model indicate that HSA is involved in the transport of copper ion. Complexes between Aβ(1–16) and copper ions have been proposed to be an aberrant interaction in the development of Alzheimer's disease, where Cu2+ is involved in Aβ(1–16) aggregation. The indexes of stability indicate that HSA removed Cu2+ from Aβ(1–16), rapidly, decreased Cu-induced aggregation of Aβ(1–16), and reduced the toxicity of Aβ(1–16) + Cu2+ significantly.